NOTARY PROCEDURE AND JUDICIAL PROCEDURE FOR THE DIVORCE WITH SPOUSES’ AGREEMENT - ANDREEA DIANA PAPA; IULIA FLORINA ŢĂPUŞ (Challenges of the Knowledge Society)
Compared to the old divorce procedures, the dissolution of marriage analysed according to the provisions of the New Civil Code (art.373-404) and the New Code of Civil Procedure (914-934) represents a real legislative innovation. Taking into consideration the judicial procedure, the legislator settles the amicable divorce, referring to spouses’ consent on the divorce, as well as to the divorce caused by one of the spouses’ poor health, and the divorce through no fault of their own. According to the new legal matters, the dissolution of marriage does not come exclusively under court jurisdiction. Thus, as far as the amicable divorce is concerned, even if the spouses have minor children, either of their own or adopted, they have at their disposal not only the judicial procedure, but also the notarial one. If the spouses do not have minor children, they can go to court, but they can also go to the notary public or to the registrar in order to certify the dissolution of marriage of their own accord. The legislator’s preference of the amicable divorce is obvious, especially as the dissolution of marriage of spouses’ own accord does no longer depend on either the length of marriage, or on their not having minor children.